PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA KEUANGAN EMITEN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2013-2015 - Amelya Dwi Kurniasasi, 12.05.52.0168; Puspitasari, Elen (Students Journal of Accounting and Banking, 2017)
This study aims to determine the intellectual capital to financial performance of the banking sector issuers listed on stock exchanges in Indonesia period 2013-2015. This study uses secondary data obtained from the financial statements www.idx.co.id. The population in this study are all banking companies that have gone public in Indonesia Stock Exchange in 2013-2015. The sampling technique was conducted using purposive random sampling. Data were analyzed using multiple linear regression analysis. The results of hypothesis testing can be concluded that the Intellectual capital has a positive and significant impact on profitability. Employed capital has a positive and significant impact on profitability. Human capital has a positive effect and no significant effect on profitability. Structural Capital had a positive effect and no significant effect on profitability. Intellectual capital and significant positive effect on productivity.Employed capital and significant positive effect on productivity. Human capital has a positive effect and no significant effect on productivity. Structural Capital had a positive effect and no significant effect on productivity. Intellectual capital has a positive effect and are not significant to the companys growth. Employed capital had a positive effect and are not significant to the companys growth. Human capital has a positive effect and are not significant to the companys growth. Structural Capital and no significant negative effect on the growth of the company.Keywords:Â Intellectual Capital and Financial Performance